Genetic rescue in an inbred Arctic fox (Vulpes lagopus) population. Issue 1875 (28th March 2018) - Hasselgren, Malin; Angerbjörn, Anders; Eide, Nina E.; Erlandsson, Rasmus; Flagstad, Øystein; Landa, Arild; Wallén, Johan; Norén, Karin
Abstract : Isolation of small populations can reduce fitness through inbreeding depression and impede population growth. Outcrossing with only a few unrelated individuals can increase demographic and genetic viability substantially, but few studies have documented such genetic rescue in natural mammal populations. We investigate the effects of immigration in a subpopulation of the endangered Scandinavian arctic fox ( Vulpes lagopus ), founded by six individuals and isolated for 9 years at an extremely small population size. Based on a long-term pedigree (105 litters, 543 individuals) combined with individual fitness traits, we found evidence for genetic rescue. Natural immigration and gene flow of three outbred males in 2010 resulted in a reduction in population average inbreeding coefficient ( f ), from 0.14 to 0.08 within 5 years. Genetic rescue was further supported by 1.9 times higher juvenile survival and 1.3 times higher breeding success in immigrant first-generation offspring compared with inbred offspring. Five years after immigration, the population had more than doubled in size and allelic richness increased by 41%. This is one of few studies that has documented genetic rescue in a natural mammal population suffering from inbreeding depression and contributes to a growing body of data demonstrating the vital connection between genetics and individual fitness.